Effectiveness of Hae-Band in Measuring Hb Levels in Postpartum Hemorrhage Risk Monitoring - Meidita, Dinda Dian; Wijayanti, Krisdiana; Hendriyani, Heni (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Postpartum hemorrhage is the main cause of high morbidity in the world (75%). Until now, efforts to early detect the risk of postpartum hemorrhage have still not been maximized. Sensor-based smartband can be the development of non-invasive methods in an effort to early detection of declining Hb levels in monitoring the risk of bleeding with practical, fast, precise, accurate, and practical. This research aims to determine the effectiveness of developing and analyzing the effectiveness of the